Tobacco use and attitudes towards tobacco control activities of Malaysian dental students - Mohd Nor, Nor Azlida; Ismail, Nurulain; Ibrahim, Farhan; Razak, Ishak Abdul; Ab-Murat, Norintan (Penerbit Universiti Sains Malaysia, 2018)
Tobacco usage among dental students and the amount of training they received may have an impact on tobacco cessation activities undertaken for their patients. This study aims to assess Malaysian dental students' tobacco use, exposure to second-hand smoke and their attitude towards tobacco control activities and curriculum. This was a cross-sectional study using a self-administered questionnaire adapted from the Global Health Professions Students Survey (GHPSS). The questionnaire was distributed to all Malaysian fourth and fifth year dental students in four public dental schools (n=372), namely University of Malaya (UM), Universiti Teknologi Mara (UiTM), Universiti Kebangsaan Malaysia (UKM) and Universiti Sains Islam Malaysia (USIM). The data were analysed using descriptive and chi square tests. In total, (n=349) respondents completed the questionnaire, yielding a 93.8% response rate. Although the prevalence of Malaysian dental students who 'ever smoked' was 21.2%, the prevalence of current smokers was low (2.3%). About 62% and 39% of students reported having been exposed to second-hand smoke in public and at home, respectively. USIM students were significantly less likely to recall having received training about approaches to smoking cessation (52.9%, p < 0.001). Significantly fewer smokers than non-smokers agreed on tobacco banning policy. Regardless of their smoking status, the majority of dental students showed positive attitudes towards dentists' role in tobacco cessation. Tobacco user among Malaysian dental students was low. There were statistically significant differences between ever smokers and non-smokers' attitudes towards tobacco banning policy. The majority of dental students showed positive attitudes towards dentists' role in tobacco cessation.